2013
DOI: 10.5935/0101-2800.20130038
|View full text |Cite
|
Sign up to set email alerts
|

Pain determinants of pain in autosomal dominant polycystic kidney disease

Abstract: Pain is the most common symptom reported by ADPKD patients, afflicting approximately 60% of cases and may result from renal hemorrhage, calculi, urinary tract infections, cyst rupture, or due to stretching of the capsule or traction of the renal pedicle. We have recently investigated pain patterns in AD-PKD patients using a translated version of a pain questionnaire specific for AD-PKD population. The questionnaire revealed that 67% patients with ADPKD exhibited some type of pain. The findings of that study em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Limited research examining the initial phase of ADPKD prior to the development of chronic kidney disease (CKD) has been published; however, there is growing evidence to suggest that patients can suffer symptoms, such as pain and fatigue, during the early stage of their disease [ 10 , 11 ]. Back pain is the most common factor leading to ADPKD diagnosis, often experienced by patients in early disease with normal renal function [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Limited research examining the initial phase of ADPKD prior to the development of chronic kidney disease (CKD) has been published; however, there is growing evidence to suggest that patients can suffer symptoms, such as pain and fatigue, during the early stage of their disease [ 10 , 11 ]. Back pain is the most common factor leading to ADPKD diagnosis, often experienced by patients in early disease with normal renal function [ 10 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Kidney stones in patients with ADPKD are associated with significant pain and morbidity. 12 In the chronic kidney disease population, patients with stones are at higher risk of end-stage kidney disease compared with patients without stones, with the suggestion that this is also true in patients with ADPKD. 13,14 For these reasons, stones should be optimally managed in patients with ADPKD.…”
Section: Introductionmentioning
confidence: 99%
“…For example, stones are a significant determinant of pain and may accelerate disease progression to ESKD in patients with ADPKD. 13,14 We conducted this systematic review to critically appraise and summarize studies which reported the incidence and prevalence of kidney stones and stone interventions in patients with ADPKD. This encompassed studies which also included patients without ADPKD as a comparator.…”
Section: Introductionmentioning
confidence: 99%
“…For example, stones are a significant determinant of pain and may accelerate disease progression to ESKD in patients with ADPKD. 13 , 14 …”
Section: Introductionmentioning
confidence: 99%